2020
DOI: 10.3390/ijerph17186642
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impact of COVID-19 Confinement and Its Relationship with Meditation

Abstract: The objective of this study was to evaluate the psychological impact of confinement due to the COVID-19 pandemic, considering any protective factors, such as the practice of meditation or self-compassion, and their relationship with different lifestyles and circumstances of adults residing in Spain. A cross-sectional study was done using an anonymous online survey in which 412 participants filled out the Depression, Anxiety and Stress Scale-2; the Impact of Events Scale; and the Self-Compassion Scale-Short For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 27 publications
5
46
0
4
Order By: Relevance
“…Our results suggested that being female was associated with increased depression, anxiety, and stress, which is similar to finding reported in previous studies [ 9 , 19 ], and similar to evidence in international literature demonstrating females tend to be more susceptible to stress and post-traumatic symptoms [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results suggested that being female was associated with increased depression, anxiety, and stress, which is similar to finding reported in previous studies [ 9 , 19 ], and similar to evidence in international literature demonstrating females tend to be more susceptible to stress and post-traumatic symptoms [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our respondents were less likely to report experiencing anxiety and stress compared to other international studies, such as those from Iran, where the prevalence of severe anxiety was 19.1% [ 18 ], and China where moderate to severe anxiety and stress were 28.8% and 29.6 %, respectively [ 19 ]. The results of this study are similar to the results of a study conducted in Spain by Jimenez O. et al, at about the same period of time [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
“…During the laboratory meetings, some engaging games were also played to overcome stress. The empowering sessions were developed based on vast knowledge, emotional intelligence, and the experience of our diverse group, as well as available literatures (World Health Organization, 2004;Shultz et al, 2016;Hendriks et al, 2017;Seyedin et al, 2019;Jiménez et al, 2020;Schlesselman et al, 2020). We compiled the following discussion topics to empower each other.…”
Section: Implementation During the Crisismentioning
confidence: 99%
“…Even physically healthy older adults experience psychological change [37]. However, anxiety increases when physical activity is low [38,39]. That is, there is a negative relationship between aging anxiety and physical activity among pre-older adults [40][41][42][43].…”
Section: The Relationship Between Physical Activity Aging Anxiety Amentioning
confidence: 99%